HUBUNGAN KADAR TIMBAL DALAM DARAH DENGAN NEUROPATI PERIFER PADA REMAJA JALANAN DI DAERAH ISTIMEWA YOGYAKARTA (DIY) - , AILEEN HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Lead is one of the main pollutants produced by burning fossil fuels activity of motor vehicles. Lead can accumulate in the air, into the human body through the digestive or respiratory tract towards the circulatory system and spread to various tissues causing impairments on the nervous system, kidneys, reproductive system, gastrointestinal tract, and anemia. These negative impacts caused a decrease in the quality of life of sufferers. Street adolescents are one of the high-risk groups of lead exposure. Motivated by the above presentation, we are interested in knowing the relationship of blood lead levels in adolescents with peripheral neuropathy in the street adolescents in DIY. Objective: To determine the relationship of blood lead levels with peripheral neuropathy in street adolescents in DIY. Methods: Data were taken from the street adolescents under the auspices of Yayasan Pinggir Jalan (Girlan) Nusantara in Yogyakarta. The study sample was 17-24 years old street adolescents, both men and women. This study uses cross-sectional study with a sample size of 55 people. The diagnosis of peripheral neuropathy disorders using Mtns and blood lead levels were analyzed by the Regional Health Laboratory of Yogyakarta. Data were analyzed using univariate and bivariate analyzes to determine the relationship between the observed variables. Results: Of the 55 street adolescents, 52 adolescents suffered from peripheral neuropathy and 3 adolescent did not suffer from peripheral neuropathy. The test results showed that sensory symptoms were found in almost all subjects (43 adolescents), followed by abnormal reflex examination results (35 adolescents), abnormal sensory examination results (28 adolescents), abnormal motor examination results (12 adolescents), and motor symptoms (6 adolescents). Bivariate analysis between blood lead levels with a total score of MTNs showed no significant relationship (p = 0,998